2020
DOI: 10.1080/23802359.2020.1773331
|View full text |Cite
|
Sign up to set email alerts
|

Complete chloroplast genome of Tulipa buhseana (Liliaceae)

Abstract: The complete chloroplast genome of Tulipa buhseana was sequenced and reported here. The circular genome of T. buhseana is 152,062 bp in length and contains 133 functional genes consisting of 87 coding sequences, 38 tRNA genes, and 8 rRNA genes. With 1 species from Smilacaceae and 1 species from Alstroemeriaceae as outgroup, phylogenetic relationships of 8 Liliaceae species based on their chloroplast genomes indicated that T. buhseana is closest to T. altaica.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Analyzing the codon preference of chloroplast genomes of 64 species in the Amaryllidaceae family, it was found that the variation range of G + C content between chloroplast genomes of different species is 0.38-0.39, with GC content less than 0.5, indicating that the GC content in chloroplast genomes of Lycoriaceae plants is less than AT content; The frequency changes of thymine T3s, cytosine C3s, adenine A3s, and guanine G3s in the third position of the synonymous codon range from 0.39 to 0.42, 0.23 to 0.25, 0.24 to 0.42, and 0.22 to 0.24, respectively; The variation range of G + C content in the third position of synonymous codon is 0.34 ~ 0.37, and the GC3s content is less than 0.5, indicating that the chloroplast genome of plants in the Amaryllidaceae family prefers to use synonymous codons ending in A/U; The range of Nec is between 54.64 and 56.16, with a higher Nec value, indicating weak codon usage bias in the chloroplast genome of Amaryllidaceae plants; The range of CAI is between 0.154 and 0.162, with a relatively low CAI value. The CBI range is between − 0.102 and − 0.079, with an average value of -0.092, indicating that there is a certain degree of preference in the chloroplast genome codons of these 64 Amaryllidaceae plants, but the preference is weak [94][95][96][97][98] .…”
Section: Codon Preference Analysis Of Chloroplast Genome Inamaryllida...mentioning
confidence: 99%
“…Analyzing the codon preference of chloroplast genomes of 64 species in the Amaryllidaceae family, it was found that the variation range of G + C content between chloroplast genomes of different species is 0.38-0.39, with GC content less than 0.5, indicating that the GC content in chloroplast genomes of Lycoriaceae plants is less than AT content; The frequency changes of thymine T3s, cytosine C3s, adenine A3s, and guanine G3s in the third position of the synonymous codon range from 0.39 to 0.42, 0.23 to 0.25, 0.24 to 0.42, and 0.22 to 0.24, respectively; The variation range of G + C content in the third position of synonymous codon is 0.34 ~ 0.37, and the GC3s content is less than 0.5, indicating that the chloroplast genome of plants in the Amaryllidaceae family prefers to use synonymous codons ending in A/U; The range of Nec is between 54.64 and 56.16, with a higher Nec value, indicating weak codon usage bias in the chloroplast genome of Amaryllidaceae plants; The range of CAI is between 0.154 and 0.162, with a relatively low CAI value. The CBI range is between − 0.102 and − 0.079, with an average value of -0.092, indicating that there is a certain degree of preference in the chloroplast genome codons of these 64 Amaryllidaceae plants, but the preference is weak [94][95][96][97][98] .…”
Section: Codon Preference Analysis Of Chloroplast Genome Inamaryllida...mentioning
confidence: 99%
“… 2020 ; Ju, Tang, et al. 2020 ). In this study, we worked on T. sinkiangensis Z. M. Mao 1980 which is a endemic species in China.…”
mentioning
confidence: 99%
“…CDS, rRNA, and tRNA genes were predicted by Prodigal2.6.3, Hmmer3.1b2, and Aragorn1.2.38, respectively (Ju et al. 2020 ).…”
mentioning
confidence: 99%